2003
DOI: 10.1897/02-452
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of polychlorinated biphenyls and polybrominated diphenyl ethers in green mussels (Perna viridis) from Singapore, Southeast Asia

Abstract: The green mussel, Perna viridis, was used in this study to measure levels of polychlorinated biphenyls (PCBs) and, for the first time, polybrominated diphenyl ethers (PBDE) in the marine environment. Samples were collected from eight different locations in the coastal waters of Singapore between April and May 2002. Forty-one PCB and 21 PBDE congeners were quantified by gas chromatography-mass spectrometry and were all positively detected in the mussel tissues. Total concentrations in green mussel tissues range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…The corresponding lipid weight based mean was 12.4 ng/g lw. The concentrations in Ost and Myt found in this work were 10−100 times lower than those in North America (9−64 ng/g, dw), 27 Korea (0.38−9.19 ng/g, wet weight), 28 Hong Kong (27.0−83.7 ng/g, dw), 29 and Singapore (2.0−38 ng/g, dw), 30 but comparable to those other Asian countries, such as India, Vietnam, Indonesia. 5,23 The relative abundances of the 12 PBDE congeners were very similar among the 11 mollusks species, with dominant congeners of BDEs 47, 71, 28, and 154, which accounted for 31.4 ± 7.9%, 15.8 ± 5.3%, 15.3 ± 11.6%, and 11.2 ± 9.7% of ∑ 12 PBDE, respectively.…”
Section: Environmental Science and Technologycontrasting
confidence: 56%
“…The corresponding lipid weight based mean was 12.4 ng/g lw. The concentrations in Ost and Myt found in this work were 10−100 times lower than those in North America (9−64 ng/g, dw), 27 Korea (0.38−9.19 ng/g, wet weight), 28 Hong Kong (27.0−83.7 ng/g, dw), 29 and Singapore (2.0−38 ng/g, dw), 30 but comparable to those other Asian countries, such as India, Vietnam, Indonesia. 5,23 The relative abundances of the 12 PBDE congeners were very similar among the 11 mollusks species, with dominant congeners of BDEs 47, 71, 28, and 154, which accounted for 31.4 ± 7.9%, 15.8 ± 5.3%, 15.3 ± 11.6%, and 11.2 ± 9.7% of ∑ 12 PBDE, respectively.…”
Section: Environmental Science and Technologycontrasting
confidence: 56%
“…Mixture toxicity and specific drugedrug interactions may be particularly important for assessing ecological risks of PhACs in marine ecosystems. In the present study, we observed residues of contaminants belonging to a variety of chemical classes, including different classes of pharmaceuticals and other consumer chemicals such as herbicides (atrazine and linuron) and bisphenol A. Additionally, other potentially toxic chemicals such as organohalogen contaminants, including organochlorines and brominated flame retardants are present at appreciable levels in this coastal system (Bayen et al, 2003(Bayen et al, , 2005. There is currently a paucity of studies describing the toxicological endpoints of PhACs and EDCs for marine organisms, especially tropical species.…”
Section: Implications For Ecological Risk Assessmentmentioning
confidence: 57%
“…Their recalcitrant nature allow them to bioaccumulate in animals, especially in top predators (Bayen et al 2003), including humans (Wolff et al 1993). SE Asia is a point source from which many key organochlorine pollutants spread to the rest of the globe through the process of evaporation and atmospheric deposition (Iwata et al 1994).…”
Section: Organochlorine Compoundsmentioning
confidence: 99%
“…PBDEs from old electronic components enter the atmosphere and eventually deposit into the water where they persist in marine animals. PBDEs are ubiquitous in the marine environment of Singapore (Bayen et al 2003) but there is little information on PBDE pollution for elsewhere in SE Asia.…”
Section: Polybrominated Diphenyl Ethers (Pbdes)mentioning
confidence: 99%